Patients’ Satisfaction on Services of Border Guard Hospital, Guimara, Bangladesh - Wahab, Md Abdul; Zafreen, Farzana; Ahmed, Mohsen Uddin; Rahman, Md Habibur; Razzak, Md Abdur (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Patients’ satisfaction is one of the established yard sticks to measure success of the hospitals. To improve the quality of services, health organizations use patient satisfaction survey to evaluate their processes delivered. A satisfied patient is more likely to develop a deeper and longer lasting relationship with their medical service providers, leading to improved compliance, continuity of care, and ultimately better outcomes. Objectives: To assess the patients satisfaction with services provided and the infrastructure facilities of Border Guard Hospital, Guimara (BGHG), of Khagrachari district Bangladesh. Materials and Methods: This descriptive cross sectional study was conducted among the patients who attended the outpatient department of BGHG from January to December 2017. Total 1340 patients aged more than 18 years, irrespective of sex, having no serious complications and willing to participate were selected by convenient sampling. Data were collected by semi-structured questionnaire by face to face interview and analyzed by SPSS 21.0. Results: Out of 1340 respondents 53.7% were serving BGB members, 18.3% were BGB families and 28.0% respondents were local residents. Majority of the patients stated that the general basic facilities at the hospital were adequate. Regarding cleanliness 94.7%, waiting room sitting facilities 91.9%, drinking water availability 88.4%, lighting arrangement 96.7%, ventilation arrangement 88.1% and toilet facilities 91.1% respondents reported that the hospital facilities were adequate. Most of the respondents were satisfied with the quality of professional services by all type of staffs of the hospital. Highest 84.9% of the respondents were satisfied with doctors’ attitude, behavior and cooperation. About other staffs; 72.9% respondents were satisfied with attitude, behavior and cooperation of nurses, 71.9% with pharmacists, 71.1% with registration clerk, 75.3%, with information desk, 70.2% with guards and 73.8% with supporting staffs. Conclusion: Patients attended at BGHG was highly satisfied about the infrastructure and the services provided the hospital. But few percentages of patients expressed their dissatisfaction. BGHG authority should keep it up and try to improve further. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 13-15